CA125 over‐release behavior following a 75‐g oral glucose test as a predictive biomarker of multidrug resistance in patients with ovarian cancer. Issue 6 (23rd March 2019) - He, Yifeng; Gu, Zhuowei; Zhu, Qiujing; Chen, Mo; He, Chenghui; Huang, Yuting; Li, Qing; Di, Wen
Abstract : Multidrug resistance is a major cause of death in patients with ovarian cancer. To improve patient survival, we developed a novel, noninvasive and convenient tool, the 75‐gram oral glucose (75gOG)‐stimulated CA125 test, to monitor cancer chemoresistance in real time. Our in vitro proof‐of‐principal experiments revealed that post‐75gOG glucose and insulin peaks can synergistically increase cancer‐derived CA125 levels, and the increase in CA125 secretion (ΔCA125) is correlated with the overactivation of the insulin receptor (IR)‐PI3K‐Akt axis and increases (ΔIC50 s) in cisplatin/taxol IC50 s. Correspondingly, among the 93 patients enrolled, post‐75gOG CA125 over‐release (i.e., enhanced ΔCA125) behavior was associated with overexpression of the IR‐PI3K‐Akt pathway and its downstream components, namely, IR, pAkt, pS6 and GLUT4, in cancer specimens. Furthermore, both pre‐ and postsurgical 75gOG CA125 tests demonstrated that CA125 over‐release showed excellent prediction efficacy on the chemoresistance potential of ovarian cancer; notably, the former indicated the need for an optimal debulking surgery, and the latter suggested the use of IR‐PI3K‐Akt inhibitors. Both test results possess independent prognostic significance for the 2‐year progression‐free survival (PFS) and overall survival (OS) of patients. The odds ratios and corresponding 95% confidence intervals (95% CIs) were 2.680 (95% CI: 1.393–5.156) for patients with CA125 over‐release behavior evidenced by a presurgical 75gOG CA125 test or 3.822 (95% CI: 1.942–7.522) for that evidenced by a postsurgical test in PFS; and 3.320 (95% CI: 1.508–7.309) for patients with CA125 over‐release behavior evidenced by a presurgical test or 5.212 (95% CI: 2.241–12.121) for that evidenced by a postsurgical test in OS. Abstract : What's new? Overactivation of the insulin signaling pathway is often underlying ovarian cancer chemoresistance but how insulin signaling is connected to the biomarker CA125 is unknown. Here the authors tested whether an oral glucose test coupled with CA125 measurements (75gOG CA125 test) can predict insulin receptor‐dependent chemoresistance. Insulin signaling stimulated CA125 secretion, and CA125 oversecretion, measured both pre‐ and postsurgically, was predictive of the chemoresistance potential, pointing to pharmacological modifiers of the insulin receptor pathway as potential additions to existing ovarian cancer chemotherapies.